My first 1000 words - Young learner's (New Delhi Young Learner's)
Reading Level 3 - 8 The adage, a picture is worth a thousand words, very clearly explains the importance of pictures in learning process. They are an excellent support for a child beginning to read and write a language. Therefore, children require an excellent and self-starter book containing colourful pictures with their names, so that they can easily learn the words by looking at their pictures. Young Learner's '1000 Words' has been developed keeping in mind the aforementioned fact and to make learning process a stressless fun. It contains 1000 words which will help a child gain confidence in building up a vocabulary. With all its child-friendly features, the book is a must-have for all!
3-8 years